Delayed-onset of progressive pseudorheumatoid dysplasia in a Chinese adult with a novel compound WISP3 mutation: a case report - Qiongyi Hu; Jing Liu; Yi Wang; Jiucun Wang; Hui Shi; Yue Sun; Xinyao Wu; Chengde Yang; Jialin Teng (BMC, 2017)
Abstract Background Progressive pseudorheumatoid dysplasia (PPD) is a rare autosomal recessive genetic disease that is characterized by pain, stiffness and enlargement of multiple joints with an age of onset between 3 and 8 years old. Mutations in the WISP3 (Wnt1-inducible signal pathway) gene are known to be the cause of PPD. Case presentation We present a case of delayed-onset PPD in a Chinese man. The 35-year-old proband presented with an almost 20-year history of pain and limitations in mobility in multiple joints. Based on the clinical manifestations, the patient was diagnosed with PPD; however, there was no specific evidence to confirm this diagnosis. Through mutational analyses, two WIPS3 mutations in exon 4, including a novel frameshift mutation (c.670dupA) in the paternal allele and an already described nonsense mutation (c.756C > A, p.Cys252*) in the maternal allele, were identified in the proband. Thus, the patient was diagnosed with PPD. Furthermore, we found that the proband's son only carried one of the mutations (c.670dupA) and therefore determined that he would not be affected by PPD in the future. Conclusions In this case, we successfully diagnosed the disease that the proband was affected precisely after the reunion of clinical diagnosis and genetic analysis. These findings demonstrate the clinical utility of genetic analysis to diagnose skeletal dysplasia and guide genetic counseling.